Morphology and photoresponse of crystalline antimony film grown on mica by physical vapor deposition - Shafa, M. (Walter de Gruyter GmbH, 2016)
Antimony is a promising material for the fabrication of photodetectors. This study deals with the growth of a photosensitive thin film by the physical vapor deposition (PVD) of antimony onto mica surface in a furnace tube. The geometry of the grown structures was studied via scanning electron microscopy (SEM), X-ray diffraction (XRD), energy-dispersive X-ray spectroscopy (EDX) and elemental diffraction analysis. XRD peaks of the antimony film grown on mica mostly matched with JCPDF Card. The formation of rhombohedral crystal structures in the film was further confirmed by SEM micrographs and chemical composition analysis. The Hall measurements revealed good electrical conductivity of the film with bulk carrier concentration of the order of 1022 Î©Â·cm-3 and mobility of 9.034 cm2/Vs. The grown film was successfully tested for radiation detection. The photoresponse of the film was evaluated using its current-voltage characteristics. These investigations revealed that the photosensitivity of the antimony film was 20 times higher than that of crystalline germanium. Â© 2016 Wroclaw university of Technology.